Antimicrobial Activity of Artemisinin and Precursor Derived from In Vitro Plantlets of Artemisia annua L. - Appalasamy, Suganthi; Kiah, Yann Lo; Song, Jin Ch’ng; Ku Nornadia, Ku Nornadia; Othman, Ahmad Sofiman; Chan, Lai Keng (Hindawi Publishing Corporation, 2014)
Artemisia annua L., a medicinal herb, produces secondary metabolites with antimicrobial property. InMalaysia due to the tropical hot climate, A. annua could not be planted for production of artemisinin, themain bioactive compound. In this study, the leaves of three in vitro A. annua L. clones were, extracted and two bioactive compounds, artemisinin and a precursor, were isolated by thin layer chromatography. These compounds were found to be effective in inhibiting the growth of Gram-positive and Gram-negative bacteria but not Candida albicans.Their antimicrobial activity was similar to that of antibactericidal antibiotic streptomycin. They were found to inhibit the growth of the tested microbes at the minimum inhibition concentration of 0.09mg/mL, and toxicity test using brine shrimp showed that even the low concentration of 0.09mg/mL was very lethal towards the brine shrimps with 100% mortality rate. This study hence indicated that in vitro cultured plantlets of A. annua can be used as the alternative method for production of artemisinin and its precursor with antimicrobial activities.